Protection of Bridges Against Stray Current Corrosion - Krzysztof Zakowski; Michal Narozny; Kazimierz Darowicki (The Baltic Journal of Road and Bridge Engineering)
A case study of Siennicki Bridge stray current corrosion hazard is presented. A corrosion risk was caused by incorrectly designed tram line traction which goes over the bridge. No dielectric insulation between running rails and bridge steel construction was used. A variety of protection methods against stray currents are described. Characteristics of the endangered bridge were described. Impressed current cathodic protection system against stray currents was proposed and designed at the Department of Electrochemistry, Corrosion and Materials Engineering, Gdansk University of Technology. Coupon technique measurements and potential measurements were performed to verify the effectiveness of the protection system.